Вербальні маніфестації концепту ЧОРНИЙ в українській лінгвокультурній парадигмі (на тлі поетичної моделі світу першої третини XX сторіччя) - Оверчук, О. Б.; Overchuk, O. B.; ORCID: http://orcid.org/0000-0003-4859-0452; Перцева, В. А.; Pertseva, V. A.; ORCID: https://orcid.org/0000-0002-5203-761X (Закарпатські філологічні студії. - 2021. - Вип. 16. - С. 144-151, 2021)
З’ясовано місце й роль концепту ЧОРНИЙ в українській мовній та поетичній картинах світу, охарактеризовано особливості його вербального вираження. Досліджено взаємодію традиційного та індивідуально-авторського начала в структурі концепту.

The article deals with the issues of describing the mechanisms of transmission of BLACK conceptual information in the Ukrainian linguocultural paradigm. The purpose of the study is to find out the place and role of the BLACK concept in the Ukrainian linguistic and poetic picture of the world, to characterize the features of its verbal manifestations. For a holistic description of the phenomenon of the BLACK concept, we used several research methods in the work, such as the method of conceptual analysis, introspection, methods of textual, semantic, comparative, linguistic and stylistic analyses. Against the background of the world poetic model in the first third of the XX century, methods of typification and systematization in the composition of the color concept of heterogeneous elements belonging to it based on the ability to constantly or accidentally express a color feature are investigated. The role of the BLACK concept in the cultural paradigm, the linguistic picture of the world, and the poetic model of the world is determined. The results of the conceptual analysis showed that the BLACK color, due to its semantic richness, the ability to accumulate the centuries-old experience of humanity, the activity of use, psychological, philosophical, cultural, ethical and aesthetic significance, is an important component of the linguistic picture of the world. Its verbal manifestations in the Ukrainian linguocultural paradigm which in any case concentrating ethnocultural, mythological and folk psychological ideas about BLACK, are characterized by a wide range of cultural meanings. It was proved that the overwhelming majority of linguistic implementations of the BLACK concept are distinguished by the ability to evoke stable associations in the mind, which ensure a uniform understanding of the meanings assigned to it by all native speakers. The concept itself acts as a universal classifier of reality, acquiring evaluative values that correlate with deep ethnopsychological signs of perception of the surrounding world, acts as an existential category, which is realized at different levels of consciousness – philosophical, psychological, moral-ethical, social.

Выяснено место и роль концепта ЧЕРНЫЙ в украинской языковой и поэтической картинах мира, охарактеризованы особенности его вербального выражения. Исследовано взаимодействие традиционного и индивидуально авторского начала в структуре концепта.
Verbal manifestations of the BLACK concept in the ukrainian linguocultural paradigm (against the background of the world poetic model in the first third of the XX century)
Оверчук, О. Б. Вербальні маніфестації концепту ЧОРНИЙ в українській лінгвокультурній парадигмі (на тлі поетичної моделі світу першої третини XX сторіччя) / Оверчук О. Б., Перцева В. А. // Закарпатські філологічні студії. - 2021. - Вип. 16. - С. 144-151. - DOI: https://doi.org/10.32782/tps2663-4880/2021.16.27.
Keywords: Мова. Мовознавство. Літературознавство. Language. Linguistics. History and Criticism of Literature. Язык. Языкознание. Литературоведение; Наукові публікації. Scientific publications. Научные публикации; мовна картина світу; linguistic picture of the world; языковая картина мира; поетична модель світу; poetic model of the world; поэтическая модель мира; вербальні маніфестації; verbal manifestations; вербальные манифестации; концепт; concept; чорний; black; черный; чорний колір; черный цвет